High-altitude large-temperature-difference bridge pier body full-hole slag concrete mix proportion design method

By using P.O 42.5 cement, different lithologic materials and polycarboxylic acid-based water reducing agents in bridge pier concrete at high altitudes, combined with specific casting methods, the problems of hydration heat and concrete shrinkage are solved, and the initial concrete is improved. The density and durability meet the production requirements of unique climatic conditions in high altitude areas.

CN119143453AInactive Publication Date: 2024-12-17THE FIRST ENG CO LTD OF CTCE GRP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411630856.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Under unique climatic conditions in high altitude areas, the design of ordinary concrete mix ratios is difficult to meet the production requirements of the full hole slag concrete on the bridge pier body, resulting in the generation of hydration heat and the shrinkage of the concrete substrate, affecting its strength and durability.

Method used

P.O 42.5 cement and different lithologic materials are used as aggregates and admixtures, and polycarboxylic acid-based water reducing agents are used to adjust the water cement ratio and dosage, combined with layered pouring and slow pouring methods to reduce hydration heat and concrete shrink.

Benefits of technology

It effectively reduces the generation of hydration heat, improves the initial density and durability of concrete, and meets the production requirements under unique climatic conditions in high altitude areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143453A_ABST
    Figure CN119143453A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a high-altitude large-temperature-difference bridge pier body full-hole slag concrete mix proportion design method which comprises the following steps: S1, taking P.O 42.5 cement as a pier body concrete raw material; s2, taking different lithologic materials as aggregate of pier body concrete; s3, the modified mountain flour minerals of different lithologic materials are adopted as admixtures of pier body concrete; s4, a polycarboxylic acid water reducing system is adopted as a water reducing agent of pier body concrete; s5, uniformly stirring and mixing the components in the pier body concrete according to the dosage to obtain a mixture, carrying out a working performance test, and verifying that the mixture meets the design requirements; the different lithologic materials comprise dolomite, slate and gneiss, the mixing amount of the admixture is 40%, and the water-binder ratio is 0.31. Generation of hydration heat is reduced, shrinkage of a concrete matrix is reduced, the initial compactness of the concrete is improved, and the problem that in the prior art, prefabrication requirements of bridge concrete in high-altitude areas are difficult to meet is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to a method for designing a mix ratio of full-hole slag concrete for a bridge pier at a high altitude and with a large temperature difference. Background Art

[0002] Bridge pier full-slag concrete refers to the resource utilization of slag produced during tunnel excavation in railway construction, which is used as aggregate for bridge pier concrete after crushing, screening and other treatments.

[0003] The construction of bridge piers in high altitude areas usually leads to a problem. The atmosphere in high altitude areas is thinner, the air density is low, and they usually have unique climate characteristics. The large temperature difference between day and night is a significant phenomenon. The drastic temperature changes, strong ultraviolet radiation, and low atmospheric pressure in high altitude areas will affect the hydration reaction rate, strength development and durability of concrete, which will make concrete prefabrication face special challenges.

[0004] At present, the ordinary concrete mix design method mainly focuses on the technology and construction characteristics of ready-mixed concrete, and pays more attention to the working performance and mechanical properties of concrete. It is difficult to meet the production requirements of full-hole slag concrete for bridge piers in high-altitude areas due to unique climatic conditions. Summary of the invention

[0005] The embodiment of the present application solves the technical problem that it is difficult to meet the production requirements of full-hole slag concrete for bridge piers in high-altitude areas under unique climatic conditions in the prior art by providing a method for designing the mix ratio of full-hole slag concrete for bridge piers with high altitudes and large temperature differences, thereby reducing the generation of hydration heat, reducing the shrinkage of the concrete matrix, and improving the initial density of the concrete.

[0006] The embodiment of the present application provides a method for designing a mix ratio of full-hole slag concrete for a high-altitude and large-temperature-difference bridge pier, comprising the following steps: using PO 42.5 cement as a raw material for pier concrete; using different lithologic materials as aggregates for pier concrete; using modified stone powder minerals of different lithologic materials as admixtures for pier concrete; using a polycarboxylic acid-based water-reducing system as a water-reducing agent for pier concrete; stirring and mixing each component in the pier concrete evenly according to the amount to obtain a mixture; performing a working performance test on the mixture, and verifying that the mixture meets the design requirements; wherein the different lithologic materials include dolomite, slate and gneiss, the admixture dosage is 40%, and the water-cement ratio is 0.31.

[0007] Furthermore, dolomite, slate and gneiss as aggregates include fine aggregate and coarse aggregate; the main technical indicators of fine aggregate include: particle size of 0-5mm, fineness modulus of 2.3, water absorption rate of <2.0%, sulfide content of <0.5%, stone powder content of ≤7.0%, void ratio of ≤2.0%, crushing value of ≤25.0%; the main technical indicators of coarse aggregate include: apparent density of ≥2500kg / m³, water absorption rate of <2%, ratio of rock compressive strength to concrete strength grade of ≥1.5, needle-like content of ≤8%, mud content of ≤1.0%, and bulk density of ≥1350kg / m³.

[0008] Furthermore, the main technical indicators of the stone powder minerals of dolomite, slate and gneiss as admixtures include: fineness ≤30%, loss on ignition ≤5.0%, chloride ion content ≤0.02%, sulfur trioxide content ≤3.0%, calcium oxide content ≤10.0%, free calcium oxide content ≤1.0%, hemihydrate calcium sulfite content ≤3.0%, water demand ratio ≤105%, and moisture content ≤1.0%.

[0009] Furthermore, the main technical indicators of the polycarboxylic acid-based water-reducing agent include: water reduction rate ≥20%, normal pressure water bleeding rate ≤20%, 30-minute slump retention value ≥180min, 60-minute slump retention value ≥150min, pressure water bleeding rate ≤90%, air content ≥4.5%, 28-day compressive strength ratio ≥120, chloride ion content ≤0.2%, sodium sulfate content ≤10%, alkali content ≤10%, and cement paste fluidity ≥240mm.

[0010] Furthermore, the maximum water-cement ratio is 0.55, the minimum cement dosage is 275Kg / m³, the maximum cement dosage does not exceed 500kg / m³, the cement dosage when preparing large volume concrete should not exceed 350kg / m³, the maximum alkali content is 1.8Kg / m³, and the maximum chloride ion content is 0.3%.

[0011] Furthermore, the performance test requirements for full-hole slag concrete entering the mold include slump of 140-180mm, air content entering the mold of 2.0%-4.0%, mold temperature <30℃, and initial setting time controlled within 15-20h.

[0012] Furthermore, the main technical indicators of PO 42.5 cement include: specific surface area of ​​300-350㎡ / kg, initial setting time of ≥45min, stability of ≤5mm, alkali content of ≤0.60%, sulfur trioxide content of ≤3.5%, loss on ignition of ≤5.0%, magnesium oxide content of ≤5.0%, and free calcium oxide content of ≤1.0%.

[0013] Furthermore, the water-cement ratio W / B is determined according to the design strength of concrete fcuo, cement strength grade fceg, cement richness coefficient γc, fly ash influence coefficient γf, and crushed stone regression coefficients aa and ab; among which, fce=γcfceg, fb=γffce, W / B=(aa×fb) / (fcuo+aa×ab×f)b, fce is the actual strength of cement, fb is the 28-day compressive strength of the mixture of cement and admixtures, f is the design strength of concrete, and b is the standard deviation of concrete strength.

[0014] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: since different rock materials are used as aggregates, the amount of cement is reduced by adjusting the mix ratio of concrete, thereby reducing the generation of hydration heat, and dolomite, slate and gneiss are used as slag to prepare high-quality aggregates, which can improve the initial density of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a flow chart of a method for designing a mix ratio of full-hole slag concrete for a high-altitude and large temperature difference bridge pier in an embodiment of the present application;

[0016] Figure 2 This is a construction flow chart of a high-altitude, large-temperature-difference bridge pier in an embodiment of the present application. DETAILED DESCRIPTION

[0017] In order to better understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0018] Reference Figure 1 A method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers comprises the following steps:

[0019] S1, select concrete raw materials.

[0020] In the specific implementation, PO 42.5 cement is used as the raw material for pier body concrete. The sulfate content in PO 42.5 cement is low, and the chloride and alkali contents meet the requirements. This type of cement is strictly controlled to meet the technical indicators when leaving the factory. The standards of the main technical indicators are shown in the following table.

[0021] Serial number Technical indicator name unit Technical index standards 1 Specific surface area ㎡ / ㎏ 300-350 2 Initial setting time min ≥45 3 Stability mm ≤5 4 Alkali content % ≤0.60 5 Sulfur trioxide content % ≤3.5 6 Loss on ignition % ≤5.0 7 Magnesium oxide content % ≤5.0 8 Free calcium oxide content % ≤1.0

[0022] In addition, the maximum water-cement ratio of cement is 0.55, the minimum cement dosage is 275Kg / m³, the maximum cement dosage does not exceed 500kg / m³, the cement dosage should not exceed 350kg / m³ when preparing large volume concrete, the maximum alkali content is 1.8Kg / m³, and the maximum chloride ion content is 0.3%.

[0023] S2, different rock materials are used as fine aggregate and coarse aggregate of concrete.

[0024] In a specific implementation, the different lithological materials include dolomite, slate and gneiss.

[0025] Among them, the standards for the main technical indicators of dolomite, slate and gneiss as fine aggregates are shown in the following table.

[0026] Serial number Technical indicator name unit Technical index standards 1 Particle size mm 0-5 2 Fineness modulus / 2.3 3 Water absorption % <2.0 4 Sulfide content % <0.5 5 Stone powder content % ≤7.0 6 Void ratio % ≤2.0 7 Crushing value % ≤25.0

[0027] Among them, the standards for the main technical indicators of dolomite, slate and gneiss as coarse aggregates are shown in the following table.

[0028] Serial number Technical indicator name unit Technical index standards 1 Apparent density kg / m³ ≥2500 2 Water absorption % <2.0 3 Rock compressive strength grade / ≥1.5 times concrete strength grade 4 Needle-like content % ≤8 5 Mud content % ≤1.0 6 Bulk density kg / m³ ≥1350

[0029] When dolomite is used as concrete aggregate, it helps to improve the durability of concrete due to its good physical and chemical stability. Slate as concrete aggregate can form an enhanced internal support in concrete due to its special layered structure, improving the compressive strength and shear strength of concrete. Gneiss is a metamorphic rock with high hardness and good physical and mechanical properties. Gneiss aggregate can be used to prepare high-strength pumpable concrete, and the mechanical properties and volume stability of concrete are related to the water absorption rate of the aggregate. The higher the water absorption rate, the lower the mechanical strength of the concrete and the greater the drying shrinkage. In addition, the use of gneiss aggregate can improve the continuity and density of concrete, which is very beneficial to improving the overall performance of concrete.

[0030] S3, stone powder mineral is used as admixture for pier body concrete.

[0031] In the specific implementation, modified dolomite, slate and gneiss are used as admixtures for the pier body concrete, and the admixture dosage is 40%, and the water-cement ratio is 0.31. In addition, the water-cement ratio W / B is determined according to the design strength fcuo of concrete, the cement strength grade fceg, the cement abundance coefficient γc, the fly ash influence coefficient γf, and the crushed stone regression coefficients aa and ab; where fce=γcfceg, fb=γffce, W / B=(aa×fb) / (fcuo+aa×ab×f)b, fce is the actual strength of cement, fb is the 28-day compressive strength of the mixture of cement and admixtures, f is the design strength of concrete, and b is the standard deviation of concrete strength.

[0032] Among them, the standards for the main technical indicators of dolomite, slate and gneiss silt minerals as admixtures are shown in the following table.

[0033] Serial number Technical indicator name unit Technical index standards 1 Fineness % ≤30 2 Loss on ignition % ≤5.0 3 Chloride ion content % ≤0.02 4 Sulfur trioxide content % ≤3.0 5 Calcium oxide content % ≤10.0 6 Free calcium oxide content % ≤1.0 7 Calcium sulfite hemihydrate content % ≤3.0 8 Water demand ratio % ≤105 9 Moisture content % ≤1.0

[0034] S4, using polycarboxylic acid as water reducing agent.

[0035] In specific implementation, the synthesis methods of polycarboxylic acid water reducers mainly include in-situ polymerization grafting method, polymerization first and then functionalization method and monomer direct copolymerization method. Polycarboxylic acid water reducers can achieve a higher water reduction rate at a lower dosage, which helps to reduce the amount of water in concrete, thereby improving the strength and durability of concrete. Polycarboxylic acid water reducers are compatible with various types of cement, maintain the slump performance of concrete, extend the construction time of concrete, and can significantly improve the early and late strength of concrete, which helps to speed up the progress of the project and improve the long-term performance of the structure. In addition, the production process of polycarboxylic acid water reducers is pollution-free, does not contain harmful substances, meets environmental protection standards, and is a green and environmentally friendly product.

[0036] Among them, the standards for the main technical indicators of polycarboxylic acid-based water reducers are shown in the following table.

[0037] Serial number Technical indicator name unit Technical index standards 1 Water reduction rate % ≥20 2 Normal pressure water bleeding rate % ≤20 3 30-minute slump retention value min ≥180 4 60-minute slump retention value min ≥150 5 Pressure water bleeding rate % ≤90 6 Gas content % ≥4.5 7 28-day compressive strength ratio % ≥120 8 Chloride ion content % ≤0.2 9 Sodium sulfate content % ≤10 10 Alkali content % ≤10 11 Cement paste fluidity mm ≥240

[0038] S5, mixing the components according to the preset amounts to obtain a mixture.

[0039] In a specific implementation, the above raw materials, including PO 42.5 cement, dolomite, slate and gneiss as coarse aggregate, fine aggregate and admixtures, water, and polycarboxylic acid-based water reducer, are put into a concrete mixer and fully mixed according to the above mix ratio requirements to obtain a mixture.

[0040] S6, verify the mixture.

[0041] In specific implementation, the working performance tests are carried out on the mixture, such as verifying the compressive strength, flexural strength, slump, durability, etc., to verify whether the mixture meets the design requirements. During the verification process, all test data and observations are recorded, and the data are analyzed to determine whether the concrete meets the design specifications and performance requirements. If necessary, the components of the concrete are further adjusted based on the analysis results.

[0042] In the specific implementation, the performance test requirements for full-hole slag concrete entering the mold include slump of 140-180mm, air content entering the mold of 2.0%-4.0%, temperature entering the mold <30℃, and initial setting time controlled within 15-20h.

[0043] The construction process of bridge piers with high altitude and large temperature difference is as follows: Figure 2As shown in the figure, in the process of pouring the pier body concrete, the layered pouring and slow pouring methods are adopted. The core idea of ​​layered pouring is to divide the concrete into several layers for construction. The pouring interval of each layer is usually 24 hours. This method can effectively avoid the temperature and shrinkage differences of concrete and reduce the risk of concrete cracking. Slow pouring can be achieved by adjusting the mix ratio of concrete or adding retarders to extend the setting time of concrete, ensure the continuity of construction and the uniformity of concrete. The appropriate pouring method should be selected according to the specific requirements and environmental conditions of the site project. In addition, the maintenance in the construction process adopts water energy moisturizing curing film, drip irrigation curing and other measures, which can effectively dissipate the hydration heat and reduce the temperature inside the concrete. In addition, the above-mentioned full-hole slag concrete mix ratio design method is used. The comprehensive application of these methods can effectively control the temperature rise of concrete during the hydration process and ensure the quality and durability of concrete.

[0044] In summary, the use of different lithology materials in high-quality cave slag as aggregates can not only reduce procurement costs and transportation costs, optimize material procurement strategies, but also reduce the amount of cement by adjusting the mix ratio of concrete, thereby reducing the generation of hydration heat. Secondly, optimizing the mix ratio of aggregates and using aggregates with larger particle sizes can reduce the amount of cement paste and further reduce the hydration temperature rise. Among them, dolomite has good physical and chemical stability, which helps to improve the durability of concrete. Slate can form an enhanced internal support in concrete, improve the compressive strength and shear strength of concrete, and the use of gneiss aggregate can improve the continuity and density of concrete, which is very beneficial to improving the overall performance of concrete. Therefore, dolomite, slate and gneiss are used as cave slag to prepare high-quality aggregates, which can improve the initial density of concrete. As a result, the technical problem that it is difficult to meet the production requirements of the unique climatic conditions in the production of full cave slag concrete for bridge piers in high-altitude areas in the existing technology is solved, and the generation of hydration heat is reduced, the shrinkage of the concrete matrix is ​​reduced, and the initial density of concrete is improved.

[0045] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.

[0046] What has been described above is only a preferred specific implementation manner of the embodiments of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can make equivalent substitutions or changes according to the technical scheme and concept of the present application within the technical scope disclosed in the present application, which should be covered by the protection scope of the present application.

Claims

1. A method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers, characterized in that: The following steps are involved: PO 42.5 cement is used as the raw material for pier concrete; Using different rock materials as aggregates for pier concrete; Modified stone powder minerals of different rock materials are used as admixtures for pier body concrete; The polycarboxylic acid-based water-reducing agent is used as the water-reducing agent for the pier concrete; Stirring and mixing each component in the pier body concrete evenly according to the amount used to obtain a mixture; Conduct working performance tests on the mixture and verify that the mixture meets the design requirements; Among them, different rock materials include dolomite, slate and gneiss, the admixture dosage is 40%, and the water-cement ratio is 0.

31.

2. A method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers as claimed in claim 1, characterized in that: Dolomite, slate and gneiss as aggregates include fine aggregate and coarse aggregate; The main technical indicators of fine aggregate include: particle size 0-5mm, fineness modulus 2.3, water absorption <2.0%, sulfide content <0.5%, stone powder content ≤7.0%, void ratio ≤2.0%, crushing value ≤25.0%; The main technical indicators of coarse aggregate include: apparent density ≥2500kg / m³, water absorption rate <2%, ratio of rock compressive strength to concrete strength grade ≥1.5, needle-like content ≤8%, mud content ≤1.0%, and bulk density ≥1350kg / m³.

3. The method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers as claimed in claim 1 is characterized in that: The main technical indicators of dolomite, slate and gneiss powdery minerals as admixtures include: fineness ≤30%, loss on ignition ≤5.0%, chloride ion content ≤0.02%, sulfur trioxide content ≤3.0%, calcium oxide content ≤10.0%, free calcium oxide content ≤1.0%, hemihydrate calcium sulfite content ≤3.0%, water demand ratio ≤105%, and moisture content ≤1.0%.

4. The method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers as claimed in claim 1 is characterized in that: The main technical indicators of polycarboxylic acid-based water-reducing agents include: water reduction rate ≥20%, normal pressure water bleeding rate ≤20%, 30-minute slump retention value ≥180min, 60-minute slump retention value ≥150min, pressure water bleeding rate ≤90%, air content ≥4.5%, 28-day compressive strength ratio ≥120%, chloride ion content ≤0.2%, sodium sulfate content ≤10%, alkali content ≤10%, and cement paste fluidity ≥240mm.

5. The method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers as claimed in claim 1, characterized in that: The maximum water-cement ratio is 0.55, the minimum cement dosage is 275Kg / m³, the maximum cement dosage does not exceed 500kg / m³, the cement dosage when preparing large volume concrete should not exceed 350kg / m³, the maximum alkali content is 1.8Kg / m³, and the maximum chloride ion content is 0.3%.

6. The method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers as claimed in claim 1 is characterized in that: The performance test requirements for full-hole slag concrete entering the mold include slump of 140-180mm, air content entering the mold of 2.0%-4.0%, mold temperature <30℃, and initial setting time controlled within 15-20h.

7. The method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers as claimed in claim 1 is characterized in that: The main technical indicators of PO 42.5 cement include: specific surface area of ​​300-350㎡ / kg, initial setting time of ≥45min, stability of ≤5mm, alkali content of ≤0.60%, sulfur trioxide content of ≤3.5%, loss on ignition of ≤5.0%, magnesium oxide content of ≤5.0%, and free calcium oxide content of ≤1.0%.

8. The method for designing the mix ratio of full-hole slag concrete for high-altitude and large temperature difference bridge piers as claimed in claim 1 is characterized in that: The water-cement ratio W / B is determined according to the design strength of concrete fcuo, cement strength grade fceg, cement richness coefficient γc, fly ash influence coefficient γf, and crushed stone regression coefficients aa and ab; among which, fce=γcfceg, fb=γffce, W / B=(aa×fb) / (fcuo+aa×ab×f)b, fce is the actual strength of cement, fb is the 28-day compressive strength of the mixture of cement and admixtures, f is the design strength of concrete, and b is the standard deviation of concrete strength.

Citation Information

Patent Citations

  • High-performance concrete for inhibiting granite gneiss alkali activity and preparation method of high-performance concrete

    CN110963766A

  • Full-hole slag phase change anti-freezing concrete and preparation method thereof

    CN118495887A

  • A high strength concrete pier construction method and the pier thereby

    KR1020120020385A